Community Participation in the Implementation of Regional Government in Indonesia - Kurhayadi (International Journal of Science and Society, 2023)
In carrying out their duties, Regional Governments generally carry out their work for the benefit of the community. However, sometimes the work of the local government does not always follow the needs of the community itself. Therefore, the community can then participate in the implementation of Regional Government. This research then aims to see how participation from the community can be carried out in the implementation of regional government. This research will be carried out using a descriptive qualitative approach. The data used in this study comes from various previous studies and studies regarding community participation in local government. The results of this study then found that community participation has been regulated explicitly in the Regional Government Law. In this Law, it is explained that the regional government needs to involve the community in the planning process as well as in the implementation of development. The form of public participation in government administration follows the principles contained in good governance.